Religion, Identity and Solidarity: Emile Durkheim's Perspective - Mustofa, Farid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study analyzes the ritual community as an association of people who try to get closer to God through religious rituals. The focus of the community is not to carry out joint rituals but on studies, sharing religious experiences, and how to increase religious obedience. There are two types of ritual communities; those formed by religious leadership and by similar interests in studying religion. This study examines the second community, by examining the values, principles, and beliefs that unite community members. Research is needed to understand religious phenomena, increase understanding, and religious tolerance. The study was conducted by library study of ritual community, in this case, the community of Salat Khusuk, and Emile Durkheim's theory contained in The Elementary Forms of the Religious Life. Descriptions, interpretations, historical continuity, internal coherence, and holistic are methodical elements in this study. The results of the study show that the attachment and social relations of the community are built by the value of identity and inward solidarity inherent in each member of the ritual community.